A Study of Influential Groups in South Tapanuli's Islamic Education Policy Process - Siregar, Mustamin; Sirozi , M.; Mukhtar, Sajida (Al-Insyiroh: Jurnal Studi Keislaman, 2024)
Education policy in South Tapanuli Regency (Tapsel) is not solely determined by the local government. Behind the scenes, a complex interplay of influential groups shapes the direction and focus of educational initiatives. This study aims to identify and analyze these key actors, examining their interactions, negotiations, and impact on education policy formulation and implementation. By delving into the political and social dynamics of Tapsel, this research seeks to provide a deeper understanding of the factors influencing educational outcomes. The study will explore how various stakeholders, including religious authorities, community organizations, educational institutions, and political parties, interact and exert their influence. The research methodology involves a comprehensive library research approach, utilizing primary data from scholarly journals, government documents, and electronic media. Through this analysis, the study will identify the most influential groups, their strategies, and their impact on specific policy areas, such as curriculum development, teacher training, and resource allocation.The findings of this research are expected to contribute to a more informed and evidence-based approach to education policy in Tapsel. By understanding the complex interplay of actors and their motivations, policymakers, educators, and community members can work together to improve educational quality, equity, and accessibility for all residents..